PC.45 Quantification of N-Acetylaspartate Concentration in the Neonatal Brain: Initial Results from the Multi-Centre Marble Study. (9th June 2014) - Lally, PJ; Pauliah, SS; Price, DL; Bainbridge, A; Addison, S; Soe, A; Pattnayak, S; Satodia, P; Wayte, SC; Ng'andwe, E; Clarke, P; Johnson, G; et al.
Abstract : Background: Early cerebral proton magnetic resonance spectroscopy (MRS) predicts medium-term outcomes in neonatal encephalopathy (NE). Metabolite peak-area ratios are most commonly used for prognosis, but conflate pathological information from different metabolites. N-acetylaspartate (NAA) is predominantly neuronal and neuronal loss should result in reduced NAA absolute-concentration ([NAA]). Thus, thalamic [NAA] should offer significant prognostic value but is difficult to measure in a clinical setting. We have established a protocol for multi-centre [NAA] measurement with the aim to use it as a surrogate biomarker in phase II clinical trials. Objective: To investigate the feasibility and utility of [NAA] quantitation across multiple centres. Design/Methods: We recruited cooled, term neonates with NE (by Sarnat grade) with parental consent across participating sites. Using various 3T scanners, thalamic MRS was performed aged 7 ± 4d (PRESS; water-suppressed TR = 2s/TE = 288/60 ms;TR/TE = 5s/60 ms; non-water-suppressed TR = 10s, TE = 60/124/205/316/495/1000 ms, ~30min acquisition). Spectra were post-processed in jMRUI and metabolite contributions determined with LCModel. [NAA] was calculated, correcting for T2 effects and cerebrospinal fluid partial volume. Results: Ten cases had sufficient data for [NAA] quantification. Sarnat grading <6h identified infants with highest [NAA] (median (IQR) 10.0(9.7–10.3) mmol/kg wet weight) as mild NE, with a lower [NAA] range for moderate NE (7.0(5.0–7.8) mmol/kg wet weight). Conclusions: [NAA] quantification is achievable in a multi-centre setting, and agrees with clinical NE grading during the therapeutic window. Follow-up examinations will allow comparison of neonatal [NAA] with later neurodevelopmental outcomes.